Development of an Automated Website Content Status Checking and WhatsApp Notification System for the Regional BAZNAS Digital Office - Muhammad Abdul Karim Luthfi; M. Rezky Revansyah Suprihono; Saeful Mu'minin; Yudhiarma; Muhammad Romadhona Kusuma (Journal of Innovation and Computer Science, 2025)
The rapid development of information technology has accelerated digital transformation in public sector organizations. In Indonesia, the National Zakat Agency (BAZNAS) has implemented a Digital Office platform to improve transparency, efficiency, and public communication by publishing news, agendas, and reports online. However, inconsistent website content updates remain a significant challenge, with many regional websites displaying outdated news, empty agendas, or even being inaccessible. This study presents the development of an automated system to check website content status and generate WhatsApp notifications to improve monitoring efficiency. The system was developed using a Rapid Application Development (RAD) approach in three stages: (1) uploading and processing the primary dataset of BAZNAS offices, automatically checking content using regular expressions and HTTP status validation; (2) incorporating a secondary dataset containing additional office information with the option to remove columns; and (3) creating structured WhatsApp messages based on predetermined content conditions and converting them into clickable wa.me links. Testing was conducted at 542 BAZNAS Digital Offices across Indonesia, resulting in a 59.62% website activity rate, incomplete content detection in 8.67% of news items and 41.70% of agenda items, and a 70% reduction in manual monitoring time. These results demonstrate the system's potential to enhance transparency, consistency, and efficiency in public sector digital transformation initiatives.